Pragmatics - Chapman, Siobhan, 1968- (Palgrave Macmillan, 2011)
"This student-friendly introduction to linguistic pragmatics explains all the major developments in core theoretical pragmatics and engages with the most recent debates in the field. It includes sections demonstrating how pragmatics can be applied to the study of literature, language acquisition and clinical linguistics"-- Provided by publisher
Keywords: Pragmatics.; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; LANGUAGE ARTS & DISCIPLINES / Linguistics / Pragmatics; LANGUAGE ARTS & DISCIPLINES / Linguistics / Semantics; Pragmatik.; Lehrbuch